Pengaruh Inovasi Produk Terhadap Kinerja Usaha Industri Kerajinan Rotan Kota Pekanbaru - Indra Safri; La Ode Syarfan (Pusat Studi Industri dan Perkotaan (PSIP) Universitas Riau, 2023)
This study aims to determine product innovation, business performance and the influence of product innovation on business performance in the rattan work industry in Rumbai District, Perkanbaru City. This research uses a type of quantitative descriptive research. This study uses a quantitative descriptive method. The data collection technique used was distributing questionnaires and conducting direct interviews with respondents. The population in this study were rattan craftsmen in Rumbai District with 36 people, while the sample was taken using a census. Data analysis was performed using simple linear regression statistical analysis. The results of research on the rattan work industry in Rumbai District, Pekanbaru City, show that product innovation is not good, business performance is not good. The product innovation variable (X) has a positive and significant effect on the business performance (Y) of the rattan handicraft industry in Rumbai District, Perkanbaru City.